The gut microbiota and its metabolites: novel therapeutic targets for inflammatory bowel disease - Shen, Xingyu; Li, Yue; Wang, Deqiang; Sun, Kang (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) pathogenesis is critically influenced by gut microbiota dysbiosis and perturbations in associated metabolites. This review outlines current IBD diagnostic and therapeutic paradigms, highlighting the persistent focus on the management of inflammatory symptoms and the absence of curative interventions. We elucidate the mechanistic links between gut microbiota dysregulation and IBD progression, with an emphasis on the immunomodulatory functions of microbial metabolites—specifically short-chain fatty acids (SCFAs), bile acids (BAs), and tryptophan (Trp) metabolism—in maintaining intestinal barrier integrity and attenuating inflammation. Furthermore, we evaluate microbiota-targeted therapeutic strategies, including probiotics, fecal microbiota transplantation (FMT), and metabolite-based interventions, as novel approaches for IBD management. This synthesis aims to inform future therapeutic development and accelerate the clinical translation of microbiota-modulating regimens.